Nucleotide substitutions in vanC-2 gene of Enterococcus casseliflavus isolates obtained from chickens. - Murase, T. (Cambridge University Press, 2002)
DNA sequencing of the vanC-2 gene was partially carried out on 10 isolates of Enterococcus casseliflavus obtained from 8 samples of imported chickens in Japan between July 1999 and June 2001 to evaluate the variation in the gene. Forty nucleotide substitutions in 36 codons were identified within 345 base pairs when compared with the vanC-2 sequence of the reference strain E. casseliflavus ATCC25788. Identical nucleotide substitutions were commonly found in the isolates recovered from chickens imported from both Brazil and China. Pulsed-field gel electrophoresis (PFGE) patterns of NotI-digested chromosomal DNA of these strains were distinguished by two, or more than six, band differences. These observations suggest that sequencing of the vanC-2 gene may be helpful for epidemiological investigation in combination with the PFGE analyses of the isolates, although particular genotypes are unlikely to be restricted to each of the countries that exported chickens.